Gastric bypass surgery alters food preferences through changes in the perception of taste. (July 2013) - Meillon, Sophie; Miras, Alexander D; Roux, Carel W le
SUMMARY Roux-en-Y gastric bypass is one of the most effective treatments for morbid obesity as it results in long-term weight loss and significant remission of obesity-related comorbidities. Although it is successful in causing weight loss, the underlying mechanisms are not completely understood. A significant decrease in calorie intake related to a shift in food preferences towards lower-calorie-dense foods has been observed after the surgery. This modification in ingestive behavior occurs through changes in the sensory and reward domain of taste. Potential mediators of these taste modifications are the exaggerated levels of gut hormones or altered gut nutrient sensing. Understanding the molecular mechanisms involved in the Roux-en-Y gastric bypass-induced taste/food preference modifications would be crucial for the development of 'knifeless' treatments.